Crack closure effect during the impact coal seam with high-pressure air blasting and the influence of gas drainage efficiency - Song, Weihua; Jiao, Huice; Wang, Yingwei (Frontiers in Earth Science, 2023)
The crack closure in the impact coal seam induced by the high pressure air blasting has a great effect on the gas drainage efficiency. The length of crack closure was calculated and analyzed based on the energy and elastic theories. Then, it was found that the closure region is located at the distance of 3.8 m from blasting hole. The high pressure air blasting experiment was conducted in the underground of one coal mine, China. The results show that the effect of crack closure on gas drainage efficiency was manifested as the amplitude of gas emission decreases at the crack closure region. In the region of 1.0 m~4.0 m from blasting hole, the amplitude of gas emission in observation hole was first increased and then decreased with the increase of distance from blasting hole. In the region of 1.8 m~2.5 m from blasting hole, the amplitude of gas emission was maximal. At the region of distance 4.0m from blasting hole, the crack was nearly closed that gas emission in observation hole was minimal. The theoretical calculation had a good consistency with the field test, and it can provide an important reference for reasonable arrangement of gas drainage boreholes.